2021
DOI: 10.1038/s41416-021-01550-3
|View full text |Cite
|
Sign up to set email alerts
|

The current status of risk-stratified breast screening

Abstract: Apart from high-risk scenarios such as the presence of highly penetrant genetic mutations, breast screening typically comprises mammography or tomosynthesis strategies defined by age. However, age-based screening ignores the range of breast cancer risks that individual women may possess and is antithetical to the ambitions of personalised early detection. Whilst screening mammography reduces breast cancer mortality, this is at the risk of potentially significant harms including overdiagnosis with overtreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 171 publications
0
57
0
1
Order By: Relevance
“…Clift el al. [ 48 ] point out the relevance of distinguishing between long-term risk prediction to guide screening strategies over a woman’s lifetime and estimating the risk of an underlying cancer being present at the time of screening. While a 5-year time frame is commonly used in models aimed at the general population, some authors propose using AI risk models with imaging data, over a 2-year timeframe, to identify women with a high probability of being diagnosed with a cancer that was missed, masked, or fast growing [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clift el al. [ 48 ] point out the relevance of distinguishing between long-term risk prediction to guide screening strategies over a woman’s lifetime and estimating the risk of an underlying cancer being present at the time of screening. While a 5-year time frame is commonly used in models aimed at the general population, some authors propose using AI risk models with imaging data, over a 2-year timeframe, to identify women with a high probability of being diagnosed with a cancer that was missed, masked, or fast growing [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms allow tailored prevention and early detection for women at higher risk[ 6 ] and possibly reduced screening for women at lower risk [ 7 ]. With no randomised controlled trial (RCT) evidence to date[ 8 ], the effectiveness of risk-stratified screening at preventing the development of higher-stage breast cancers is being tested internationally in the WISDOM and MyPeBS trials[ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review published in 2013 found that it is unclear if mammographic screening does more good or harm (Gøtzsche & KJ, 2013). Recent studies suggest that mammographic screening could be most effective if offered based on the personal risk of the patient calculated from family history, breast density, reproductive factors, demographic, clinical, imaging-related and genetic data (Clift et al, 2021). This highlights the great importance of genetic testing in identifying high risk individuals for screening and early detection.…”
Section: Introductionmentioning
confidence: 99%